Hydraulic overload of upflow anaerobic sludge bed reactor treating landfill leachate - Gabr, Tarek Zeiad (University of Ottawa (Canada), 2003)
The impact of hydraulic shockloads on UASB reactors operating at mesophilic conditions (T = 35°C) was studied. The wastewater, landfill leachate, was pretreated by filtering it through peat moss. The reactor was 1/2 filled with sludge previously acclimated from a pulp mill wastewater treatment facility. The shockloads imposed on the reactor were hydraulic where the flowrate of the influent wastewater was increased by 2--3 times the initial flow rate at quasi steady-state (corresponding to a change of HRT from 2.5--3 to 1--1.5 d) where the influent concentration was maintained around 10 g COD/L. Two modes of shock-loading were compared: continuous versus intermittent for a total duration of 3 hours, where the intermittent operation distributed the flowrate increase over 9 hours to make a total of 3 hours. The results showed that a UASB reactor can endure a single shockload of OLR close to 9.6 +/- 1.8 g COD/L.d and recover to pre-shock conditions in a period not exceeding 30 hours. Intermittent shock feeding resulted in better effluent quality; nonetheless, it took a longer time to recover, and was more prone to solids washout. (Abstract shortened by UMI.)
Keywords: Engineering, Chemical.; Engineering, Sanitary and Municipal.